2003
DOI: 10.1074/jbc.m210751200
|View full text |Cite
|
Sign up to set email alerts
|

Rib72, a Conserved Protein Associated with the Ribbon Compartment of Flagellar A-microtubules and Potentially Involved in the Linkage between Outer Doublet Microtubules

Abstract: Ciliary and flagellar axonemes are basically composed of nine outer doublet microtubules and several functional components, e.g. dynein arms, radial spokes, and interdoublet links. Each A-tubule of the doublet contains a specialized "ribbon" of three protofilaments composed of tubulin and other proteins postulated to specify the three-dimensional arrangement of the various axonemal components. The interdoublet links hold the doublet microtubules together and limit their sliding during the flagellar beat. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 65 publications
9
95
0
3
Order By: Relevance
“…In Chlamydomonas and likely also mammals, DM10 domain-containing proteins are tightly bound to the flagellar doublet microtubules [Patel-King et al, 2002;Ikeda et al, 2003;Ikeda et al, 2005]. This suggests that DM10 domains might act as flagellar NDK regulatory modules or as units specifically involved in axonemal targeting or assembly.…”
Section: Structural Features Of the Dm10 Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…In Chlamydomonas and likely also mammals, DM10 domain-containing proteins are tightly bound to the flagellar doublet microtubules [Patel-King et al, 2002;Ikeda et al, 2003;Ikeda et al, 2005]. This suggests that DM10 domains might act as flagellar NDK regulatory modules or as units specifically involved in axonemal targeting or assembly.…”
Section: Structural Features Of the Dm10 Domainmentioning
confidence: 99%
“…A recent report suggested that JME may be caused by mutations in the EFHC1 gene [Suzuki et al, 2004]. Here I will discuss the evidence supporting a role for Efhc1 in JME and detail recent analyses [Ikeda et al, 2005] that demonstrate that this protein is the mammalian orthologue of Chlamydomonas Rib72 and as such is likely an integral axonemal component [Patel-King et al, 2002;Ikeda et al, 2003] located within the protofilament ribbons [Ikeda et al, 2003] and, potentially, is also present in basal bodies/centrioles [Hinchcliffe and Linck, 1998;Keller et al, 2005]. These studies have raised the exciting possibility that alterations in ciliary function due to mutations in Efhc1/Rib72 provide the underlying basis for this inherited neural disorder.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations